Simulation in Single and Multi-Flow Direction of Airflow Sensor - Che Abdullah, Sukarnur; Dzulhelmy bin Amari, Mohamad; Shafiq bin Abdullah Sabil, Amirul; ., . (International Journal of Engineering and Technology, 2018)
This paper investigates simulation of air flow acting on the airflow sensor using the Computational Fluid Dynamic (CFD) approach. Simulation is carried out to evaluate the performance of airflow sensor by analysing small change of the air flow acting on the airflow sensor structure. Identification of the characteristics and parameters for the sensor in motion was done to achieve higher accuracy of the airflow result. Analyzation stage from the obtained data comprehending the behaviour of the airflow in higher accuracy while sensor in motion will be verified by detection of high sensitivity in relative velocity of the airflow sensor compared to conventional sensor. Therefore, an analysis was conducted with three different airflow directions involving necessary boundary condition and parameter. The efficiency from the tabulated data for dynamic motion has also been determined by comparing simulation data with calculation. All simulations and analyses were completed using the ANSYS software.Â